Enhancing academic essay writing through the effective use of checklist - Baharuddin, Khairul Hisyam; Mohd Nasir, Nazatul Syima; Stark, Alexander (Academica Press Solutions, 2023)
Many students struggle to meet the rigorous standards and expectations of scholastic writing, despite the importance of academic essay writing skills to students' academic success. Consequently, the resulting essays frequently lack coherence, organization, and adherence to academic standards. Inadequate writing skills not only hinder students' ability to convey their ideas and arguments effectively, but also have a negative influence on their overall academic performance. Therefore, it is imperative to address this issue and provide effective interventions that can improve students' writing skills and enable them to produce high-quality academic essays. This study examines the use of criteria to improve academic essay writing. This study aims to examine how the systematic implementation of criteria can improve students' writing skills, cultivate critical thinking, and enhance the overall quality of academic essays. Through an exhaustive literature review, this paper demonstrates the effectiveness of checklists in supporting students' writing processes, ensuring adherence to academic standards, and facilitating self-assessment. The findings highlight the benefits of incorporating criteria into academic writing pedagogy as well as the need for further research and implementation in educational settings.